Total quality: creating individual and corporate success - Ahluwalia, J.S. (New Delhi: Institute of Directors, 1996)
The world congress on total quality has earned the reputation of being the biggest quality event in Asia. and draws all top Quality gurus and professionals from accross the world. The compilation of papers being presented during the 6th world Congress on total Quality being held at New Delhi, brings out the state of the art knowledge in almost every conceivable area of quality management.
Total quality sate of the art -- TQM-The global challenge -- Implementing TQM -- Changing corporate culture -- Human side of quality -- TQM implementation-Indian experience -- TQM-International experience -- Customer care -- Benchmarking & business process re-engineering -- statistical process control -- Quality standards, certification & Accreditation -- Auditing -- Education & training for quality -- Quality in R and D -- Quality in healthcare -- Qs 9000 :the automotive requirement -- Quality in software -- TQM-The future trends.
Keywords: Quality management; Quality; Corporate success